EFFORTS TO INCREASE STUDENTS’ LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING MODEL ON THE MATERIAL OF THE EFFECTS OF HEAT ON CHANGES IN THE FORM OF OBJECTS IN CLASS V AT SDN 112 PALEMBANG - Anisa Resti Latifah; Vinencia Ika Indralin; Siti Dewi Maharani (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This research is a class action research (CAR) conducted in class V SDN 112 Palembang. This research was conducted in class V A with a total of 25 students consisting of 12 boys and 13 girls. This study aims to improve the learning outcomes of students on the science content of the material of the effect of heat on changes in the forn of objects by using the problem based learning model in class V A SDN 112 Palembang. Data collection techniques in this research used test and nontest. I the form of observation and documentation. Pre-cycle results with KKM 70, the acquisition of scores obtained by students is still a lot below KKM, <70 there are 21 students and there are 4 completed students. Based on the results of this research, the action on cycle 1 using the model problem based learning has reached the KKM score of 64% of all student with an average of 70.8. Aplication of cycle 2 increased to 96% with an average of 90.8. This suggest that the application of the problem based learning model in the science content of the material of the effect of calor on changes in the form of objects in the class V A at SDN 112 Palembang can improve the learning outcomes.